Pengembangan Roll Burnishing dengan Penambahan Bola Bearing pada Kualitas Permukaan Hasil Pembubutan Mild Steel ST37 - Patulak, Frengky Sulo; Musa Bondaris Palungan; Nitha (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2025)
The turning process is a primary method in the manufacturing industry for producing components with high accuracy and surface quality. However, the results of turning often require additional finishing processes to achieve the desired surface roughness. This study employs the roll burnishing technique with the addition of ball bearings to enhance the surface quality of mild steel (ST37) after turning. The research analyzes the effects of spindle speed variation (70–1255 RPM) and depth of cut (0.2–1.4 mm) on surface roughness, as well as the correlation between these two parameters. The methods used include experiments with parameter variations, surface roughness measurements using a Surface Roughness Tester, and statistical analysis through linear regression and ANOVA using SPSS. The results indicate that spindle speed significantly affects surface roughness (R² = 0.758), with higher speeds reducing roughness. The depth of cut also has a strong influence (R² = 0.911), with increased depth reducing roughness. The combination of both parameters explains 74.4% of the variation in surface roughness. These findings provide practical guidance for the industry to optimize roll burnishing parameters to improve surface quality and production efficiency.